Optimized design for flexible polymer thermoelectric generators. (5th June 2016) - Aranguren, P.; Roch, A.; Stepien, L.; Abt, M.; von Lukowicz, M.; Dani, I.; Astrain, D.
Highlights: A polymer π-shaped module has been printed and tested under different conditions. A model able to simulate the behavior of polymer TEG has been developed. The validated model has been used to geometrically optimize the polymer module. The power production by the optimized design has been increased 50 times. Up to 21.73 MW h/year can be produced by a polymer TEG in a real application. Abstract: Intrinsically conducting polymers are cheap, flexible, environmentally friendly and easy to manufacture. These characteristics and their low thermal conductivity make them suitable for thermoelectric generation. In this study a PEDOT:tos-Silver thermoelectric module (TEM) has been printed and tested. A computational model able to simulate the behavior of polymer thermoelectric generators (TEGs) has been developed and validated with the experimental data. The validated computational model has been used to geometrically optimize the power generation of the polymer TEM. The π-sectional area of the p-type and n-type legs, their length and the number of thermocouples have been modified obtaining an improvement of 50 times the power generated by the printed module, the base design. The optimized geometry has been studied into a real application scenario of waste heat harvesting, a tile furnace with a smoke mass flow of 6.39 kg/s and a temperature of 187 °C. The thermoelectric generation of the polymer TEG located at the exhaust of the tile furnace ascends to 21.73 MW h/year. In comparison with the bismuth-telluride commercial modules, the polymer production is six times lower, however, the advantages of the polymers materials over the commercial modules make them suitable for thermoelectric generation.